Quality Assurance Strategies and Teachers’ Productivity in Public Secondary Schools in Lagos State, Nigeria - Ajao, R. L.; Obiwumi, T. S.; Alabi, R. M.; Omosidi, A. S. (International Journal of Educational Management, 2022)
This study examined quality assurance strategies and teachers’ productivity in Lagos State public secondary schools, Nigeria. The research design adopted for this study was a descriptive survey of correlational type. Stratified random sampling technique was used to select 300 (50 principals and 250 HODs) out of the 1,944 principals and Heads of the Departments in the 324 public secondary school in Lagos State. Research instruments titled: “Quality Assurance Strategies Questionnaire” (QASQ) and “Students’ Academic Performance Proforma” (SAPP) were used to obtain relevant data.The instrument (QASQ) was validated through face and content validities while the reliability coefficient of the instrument was 0.81. Four research questions were raised and one hypotheses were formulated to guide the study. Descriptive statistics of percentage and mean were used to answer the research questions while Stepwise Multiple Regression statistic was used to analyze the formulated hypothesis at 0.05 level of significance. The findings revealed that there was a significant relationship between quality assurance strategies (supervision, training and development programme and teachers’ adequacy) and teachers’ productivity in Lagos State public secondary schools (r val.= .634 and p-value= .011< .05). Based on the findings of the study, it was recommended among others that; External supervisors should improve on their visitation to secondary schools in Lagos State. Also, Lagos State secondary school principals are urged to regularly carry out supervision so as to serve as professional guidance to teachers in order to improve their competencies for effective teaching process.